2004
DOI: 10.1016/j.steroids.2003.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of estrogen-induced ERK 1 and 2 activation via multiple membrane-initiated signaling pathways

Abstract: Estradiol (E2) and other steroids have recently been shown to initiate various intracellular signaling cascades from the plasma membrane, including those stimulating mitogen-activated protein kinases (MAPKs), and particularly extracellular-regulated kinases (ERKs). In this study we demonstrated the ability of E2 to activate ERKs in the GH3/B6/F10 pituitary tumor cell line, originally selected for its enhanced expression of membrane estrogen receptor-alpha (mERalpha). We compared E2 to its cell-impermeable anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(132 citation statements)
references
References 65 publications
10
119
0
Order By: Relevance
“…Rather our findings suggest that E 2 's effects on mast cell mediator release are through a membrane-associated (non-genomic) form of ER-α. This type of ER stimulation has been shown to induce rapid cellular responses through G-protein activation, (Bulayeva et al, 2004;Collins and Webb, 1999;Doolan et al, 2000;Improta-Brears et al, 1999;Stefano et al, 1999;Watson et al, 1999) which can include various signaling pathways involving Ca 2+ fluxes, and modulation of mitogen-activated protein kinases and adenyl cyclase (Bulayeva et al, 2004;Collins and Webb, 1999;Doolan and Harvey, 2003;Nadal et al, 2000;Song et al, 2004;Zivadinovic et al, 2005). Indeed, we found that intracellular Ca 2+ was increased within the first 2.5 min after estrogenic stimulation of RBL.…”
Section: Discussionsupporting
confidence: 49%
“…Rather our findings suggest that E 2 's effects on mast cell mediator release are through a membrane-associated (non-genomic) form of ER-α. This type of ER stimulation has been shown to induce rapid cellular responses through G-protein activation, (Bulayeva et al, 2004;Collins and Webb, 1999;Doolan et al, 2000;Improta-Brears et al, 1999;Stefano et al, 1999;Watson et al, 1999) which can include various signaling pathways involving Ca 2+ fluxes, and modulation of mitogen-activated protein kinases and adenyl cyclase (Bulayeva et al, 2004;Collins and Webb, 1999;Doolan and Harvey, 2003;Nadal et al, 2000;Song et al, 2004;Zivadinovic et al, 2005). Indeed, we found that intracellular Ca 2+ was increased within the first 2.5 min after estrogenic stimulation of RBL.…”
Section: Discussionsupporting
confidence: 49%
“…This could reflect membrane steroid receptors in two different lipid compartments in the plasma membrane (such as rafts vs. invaginated caveolae or rafts vs. non-raft membrane [37;50;51]), but this has not been directly demonstrated. These potent responses (at the pM to nM concentrations range, [40]) contrast dramatically to the μM-mM effective concentrations required for genomic responses, and also used for studies on ERK activation by others [25]. In other studies we also showed that inhibitors of signaling pathways that lead to ERK activation inhibit both E 2 -and xenoestrogen-induced kinase phosphorylation [22].…”
Section: Estrogens and Xenoestrogens Can Rapidly Activate Oscillatingmentioning
confidence: 78%
“…First, we directly examined the ability of E 2 and xenoestrogens to raise intracellular Ca ++ levels, as Ca ++ signaling is likely to be involved in other downstream events, including both ERK activation [40] and regulation of secretion of peptide hormones like PRL [43]. E 2 , E 2 -P (E 2 conjugated to peroxidase to impede its entry into cells), and all xenoestrogens caused increased Ca ++ spikes at low concentrations [24;41].…”
Section: Results E 2 and Xenoestrogens Can Rapidly And Potently Elicimentioning
confidence: 99%
See 2 more Smart Citations